New-found Means Used for judicial notices in the Jordanian Civil Procedure Law - Aladwan, Ashraf; Alisa, Isam; Abuelghanam , Saad A. S. (Dirasat: Shari'a and Law Sciences, 2022)
Objectives: This study aims to trace and examine the new amendments enacted by the Jordanian legislature to govern the administration of judicial notices, in order to evaluate its advancement and the challenges they create as well as the solutions they introduce. The following are among the new electronic means to come into force, as announced by the Justice Minister, in service of civil judicial notices: emails, SMS, and the lawyer’s personal email. Methods: This study utilizes an inductive and analytical methodology through analyzing the rules of the Amended Civil Procedures Law No. (31) Of 2017, and the Amended Law No. (4) Of 2019. Additionally, it analyzed the system of using electronic means in Civil Judicial Procedures No. (95) of 2018 and the public notice by the head of the Judicial Council distributed to the heads of courts and to the attorneys public divisions ordering that judges must start utilizing electronic means on the 16th of September 2019. Results: The study reached to the following results that the new amendments are insufficient to achieve the desired objectives sought in tackling the practical issues sustained in the service of judicial notices. Conclusions: The new rules need to be reviewed to address a number of matters including nullification of legal notices, content of text messages and using the same means to other judicial procedures such as memoranda and pleas.